2017
DOI: 10.1111/jeb.13132
|View full text |Cite
|
Sign up to set email alerts
|

The role of recombination in evolutionary adaptation of Escherichia coli to a novel nutrient

Abstract: The benefits and detriments of recombination for adaptive evolution have been studied both theoretically and experimentally, with conflicting predictions and observations. Most pertinent experiments examine recombination's effects in an unchanging environment and do not study its genomewide effects. Here, we evolved six replicate populations of either highly recombining R or lowly recombining R E. coli strains in a changing environment, by introducing the novel nutrients L-arabinose or indole into the environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 112 publications
(178 reference statements)
0
9
0
Order By: Relevance
“…For each study, we counted the number of non-synonymous mutations in TFs and TGs relative to the number of corresponding sites. 4 (29,34,35,39) out of 13 ALE studies (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) had a significantly higher number of mutations in TFs than expected whereas none of the MA studies passed the significance test ( Fig. 5) (P One-sided Fisher's exact < 0.05 ).…”
Section: A B C Dmentioning
confidence: 88%
See 3 more Smart Citations
“…For each study, we counted the number of non-synonymous mutations in TFs and TGs relative to the number of corresponding sites. 4 (29,34,35,39) out of 13 ALE studies (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) had a significantly higher number of mutations in TFs than expected whereas none of the MA studies passed the significance test ( Fig. 5) (P One-sided Fisher's exact < 0.05 ).…”
Section: A B C Dmentioning
confidence: 88%
“…Depending on the mode of action of the targeted drug(s) in a study, mutations may only be selected in a specific enzyme, in which case, an excess of TF's mutations would not be observed. This also holds for studies on auxotrophs (30). Often though, when a study focused on cross-resistance or on a drug with multiple mechanisms, selected mutations were more frequently among TFs (33,34,37) (Table S7, supplementary file 1).…”
Section: A B C Dmentioning
confidence: 96%
See 2 more Smart Citations
“…In work by McDonald et al 21 the ability of yeast to purge hitchhikers was demonstrated using sequence-level dynamics. Additionally in a recent work by Chu et al 29 using the genderless and an HFR control strains we had previously developed, a recombination event during in situ adaptive evolution was observed for the first time; however, the relative fitness impacts of the individual mutations and recombinants were not determined, thus the exact benefits of recombination were not fully assessed. In this work, we identified a specific case of a sexual recombination event that likely helped to maintain a weaker beneficial mutation (mutations in cyaA ) in the sexual population.…”
Section: Discussionmentioning
confidence: 99%